Comparison of the homemade and commercial graphene in heightening mechanical properties of Al2O3 ceramic. Issue 2 (1st February 2017) - Zhang, Liu; Wang, Zhi; Wu, Junyan; Shi, Guopu; Xu, Hanqing
Abstract: Graphene has been successfully fabricated by a novel method, using graphite powder and NMP (N-Methyl Pyrrolidone) as the raw materials based on the principles of liquidoid exfoliation and mechanical milling. SEM, TEM and Raman spectrum were utilized to characterize the morphology of the homemade graphene, illustrating the few defects and rare layers were endowed in this study. Afterwards, the homemade and commercial graphene were doped into Al2 O3 powder with the mass ratio of 0%, 1%, 2%, and 3% to reinforce the mechanical properties of the matrix. The composites were processed at 1600 °C, pressure of 30 MPa and soaking time of 1 h by vacuum hot pressing. The test results illustrated the bending strength and fracture toughness tended to be intensive at first and subdued afterwards, achieving the optimal performance of 625.4±18.2 MPa and 6.07±0.22 MPa m 1/2 at 2 wt% prepared graphene additive, and the commercial grapheme owned the best heighten effect in 3 wt% graphene/Al2 O3 composites. Compared to the blank Al2 O3 sintered samples, the graphene/Al2 O3 specimens (both prepared and commercial additive) behaved evident increase in mechanical properties, even upon 30% enhanced in fracture toughness and bending strength generally by the prepared grapheme. Moreover, the prepared graphene had better improvement effect than commercial graphene in enhancing mechanical properties of Al2 O3 ceramic.